Whatsapp Marketing Strategy Through An Interpersonal Communication Approach In Increasing Sales At Raja Kurma Bengkulu - Mira Apriani; Rahma Santhi Zinaida; Isnawijayani Isnawijayani; Zaid Amin (UNIVED Press, 2025)
Marketing strategies are essential to inform and understand consumers about the sustainability of economic activities. Entrepreneurs use advertising, direct marketing, personal selling or promotion, and other marketing communication tools to increase sales. Integrated marketing strategy (IMC) and the AISAS Model are two strategic options that can be used for the marketing communication process in the digital era. Through the collaboration of the AISAS Model and IMC Strategy which are the general basis for obtaining a more targeted database, media is needed that can gather consumers in one more in-depth personal information center. The most popular personal social media currently used by the Indonesian people is WhatsApp Business media. This study uses a descriptive qualitative approach to explain and describe the phenomena that occur in the Raja Kurma Bengkulu WhatsApp advertising communication. This study also uses a quantitative approach with the descriptive statistics method. The results of the study show that digital marketing activities carried out can help increase the number of Raja Kurma Bengkulu databases. The number of posts has a weak negative correlation, not significant. Save Contacts has a very strong correlation, not significant. The number of Organic Interactions has a strong correlation, not significant. Reply Chat has a very strong correlation, not significant and View Posts has a very strong correlation, approaching significant.